Lysimachia Capillipes Inhibit Adipogenesis via Angiogenesis Inhibition - Li, Xiumin; Xue, Yu; Pang, Liang; ShangGuan, Zhaoshui; Pan, Yutian (Drug Research, 2019)
Obesity is a common and increasingly prevalent human condition due to unhealthy diet and less-exercise lifestyle. Development of obesity is associated with substantial modulation of adipose tissue structure. The expansion of adipose tissue is linked to the development of its vasculature, and modulation of angiogenesis may have the potential to impair adipose tissue development. In this study, we used obesity model of zebrafish fed by egg yolk to investigate the effect of Lysimachia capillipes on the obesity. The results showed that Lysimachia capillipes inhibited angiogenesis of adipose tissue in transgenic zebrafish Tg (Fli 1: EGFP), which was similar to surppressing effect of TNP-470, which was accompanied by decreased Oil Red O staining of the zebrafish. The treatment of Lysimachia capillipes reduced expression of MTP significantly, but modestly reduced expression of Ppar g, FABP10a, and CD36 level through ISH, which was accordant with the results by PCR analysis. The study proved that Lysimachia capillipes might possess novel therapeutic properties for prevention and treatment of obesity.
Keywords: Lysimachia capillipes; adipogenesis; angiogenesis; fat metabolism